A Bibliometric Approach to Existing Literature on Teleworking - Cruz-Cárdenas, Jorge (2024)
Teleworking or telecommuting implies that employees perform their duties mainly from home or outside the facilities of the organizations to which they belong. The growth of academic and scientific interest in teleworking has accelerated markedly since the Covid-19 pandemic. The present study contributes to the academic research area of teleworking by organizing and structuring existing knowledge using a bibliometric approach. This study has selected Scopus as a database, and the applied search strategy has generated 8,692 documents. The descriptive analyses (using performance measures) conducted on this body of literature have confirmed the rapid increase in academic and scientific publications. The results indicate that the research on teleworking can be characterized as a multidisciplinary field, where the institutions and universities of developed countries play a leading role. Science mapping establishes the following four areas of research: 1) technological aspects that support teleworking, 2) advantages and disadvantages of teleworking, 3) human aspects of teleworking, and 4) Covid-19, teleworking, and home. The analysis of overlay visualization of terms helps identify the historical evolution of the topics of interest. This evolution starts from issues focused on technology and then addresses the issue of the human being as the center of interest. In recent years, the interest has focused on the Covid-19 pandemic. Finally, the present work discusses these research results and provides guidelines for future studies.